"Dear Alex" an online interactive digital comic about autism - Arceo, Klaudine Paola C.; Austria, Romanlito S. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
Autism is a social disorder that was first identified by Leo Kanner. Autism is a growing disorder in the world today and even though there is more information about the disorder, researchers are still unable to truly uncover what causes autism. For people diagnosed with autism, they have trouble in socializing with others, and the severity of their autism determines how they interact with others. In the diagnosis of a person with autism, there is a behavioral checklist that doctors look out for. According to the World Health Organization (WHO), autism becomes evident on children from ages 5 or below. There are number of social behaviors that can be identified as autism and the American Psychiatric Association has determined that autism is a spectrum and a number of traits can be seen in the Autism Spectrum Disorder (ASD) umbrella such as asperger syndrome.

Autism is more well-known now than it was in the past. However, there is still misunderstanding about the disorder and it may lead to the hindering of an autistic person's growth and be subject to some discrimination. In the Philippines, there are schools or centers that help support families with autistic relatives and help them get through life. In my research for this study, I have found that comics is one way to effectively share stories and in recent years, the style of Japanese comics, commonly known as manga and animation known as anime have become popular that it has become a common style found in local comics today such as Black Ink Publishing and other independent comics. With the use of current technology and more prominent use of social media, spreading information has been easier. Developing a digital comic about autism may be able to build curiosity from people to know more about autism through a story narrative.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 67-74
Keywords: Autism; Autism -- Webcomics; Autism Spectrum Disorder (ASD)